EFFECT OF ALUMINIUM WASTE POWDER ON THE STRENGTH PROPERTIES OF CEMENT MORTAR - Aadil Hameed; Sajjad Ali Mangi; Muhammad Rehan Hakro; Arun Kumar; Syed Muhammad Husnain; Abdullah Khan (NAROTAMA UNIVERSITY, Indonesia, 2023)
The cement is used as primary binding material in the field of civil engineering is undoubtedly at a higher level due to the increase in urbanization. Concrete, cement mortar, and other composite building materials are made from it. The substantial use of OPC in the field of construction industry has increased the production of CO2. This has huge negative impact on the environment and has encouraged everyone to explore and analyze practical advancement by substituting alternative waste products in concrete and mortar. Therefore, the objective of this study was to evaluate the strength performance of cement mortar containing Aluminium waste powder as a Cementitious Material. In this study, we have substituted the cement with different percentages i.e., 2.5% to 10% of Aluminium waste powder to obtain feasible mortar mix. The cubes of 50 mm size were cured for 3, 7, and 28 days, the properties of flowability, density, and compressive strength was studied. The results indicated that by increase in addition of Aluminum waste powder (AWP) flowability of mortar paste decreased, the water cement ratio was fixed as 0.50 for all type of mixes. The results indicated that the Density and Compressive Strength of Cubes cured in water, it was observed that as the % Addition of AWP increased the density and compressive strength of cubes cured were reduced. For Compressive Strength, it was found that at each designated day, the compressive strength of cubes up to 2.5% addition has given suitable value but intensely decreased at 10% addition. At 2.5% Addition Aluminium waste powder on 28th day test it was noticed that it has greater value of compressive strength for all % of addition.